2020
DOI: 10.1177/1039856220908172
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio – a simple, accessible measure of inflammation, morbidity and prognosis in psychiatric disorders?

Abstract: Objective: A narrative review to describe the utility of the neutrophil-lymphocyte ratio (NLR) as an inflammatory marker in psychiatric and non-psychiatric disorders and to discuss the potential role of NLR in psychiatric research. Conclusions: NLR is inexpensive and readily available using division of two measures obtained on routine blood testing. NLR is elevated in a number of psychiatric disorders. It can predict morbidity and mortality in a wide range of non-psychiatric conditions, but this has not been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
1
16
0
2
Order By: Relevance
“…In addition, several papers have reported that NLR was correlated with other markers of inflammation, such as C Reactive Protein (CRP) and IL (interleukin)-6, or with oxidative stress markers (i.e., total oxidative status, total thiol) [25][26][27][28]. NLR, PLR and MLR have been studied in psychiatric disorders, including MDD and BD [24]. Numerous studies have established NLR and PLR as biomarkers for the manic phase of bipolar disorder [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several papers have reported that NLR was correlated with other markers of inflammation, such as C Reactive Protein (CRP) and IL (interleukin)-6, or with oxidative stress markers (i.e., total oxidative status, total thiol) [25][26][27][28]. NLR, PLR and MLR have been studied in psychiatric disorders, including MDD and BD [24]. Numerous studies have established NLR and PLR as biomarkers for the manic phase of bipolar disorder [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…An increased count of neutrophils reflects the intensity of inflammatory response and a decreased count of lymphocytes represents the immune system impairment [ 23 ]. These ratios are low-cost and readily available parameters that can be calculated from routine complete blood count [ 24 ]. In addition, several papers have reported that NLR was correlated with other markers of inflammation, such as C Reactive Protein (CRP) and IL (interleukin)-6, or with oxidative stress markers (i.e., total oxidative status, total thiol) [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a similar prognostic measure has not been developed in psychiatry yet. It was suggested to investigate whether NLR is similarly predictive in psychiatric disorders with prospective studies and to determine whether it is used in clinical practice [ 40 ]. A study in the literature evaluated the relationship between NLR and depression-anxiety levels in patients with COVID-19, and this study reported no relationship between depression-anxiety scores and NLR-CRP levels [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psikiyatrik bozukluklarda tam kan sayımı (TKS) parametreleri hakkında son yıllarda çeşitli çalışmalar yapılmıştır. Psikotik bozukluklar ve nevrotik bozukluklarda yapılan çalışmalarda önemli bulgulara ulaşılmıştır (1,2). Şizofreni (1), bipolar bozukluk (BB) (3), major depresif bozukluk (MDB) (4) ve madde kullanım bozukluğu (MKB) (5,6), TKS ile ilişkisi sıklıkla araştırılmış psikiyatrik bozukluklardır.…”
Section: Introductionunclassified
“…Psikotik bozukluklar ve nevrotik bozukluklarda yapılan çalışmalarda önemli bulgulara ulaşılmıştır (1,2). Şizofreni (1), bipolar bozukluk (BB) (3), major depresif bozukluk (MDB) (4) ve madde kullanım bozukluğu (MKB) (5,6), TKS ile ilişkisi sıklıkla araştırılmış psikiyatrik bozukluklardır. Anksiyete bileşeni olan psikiyatrik bozukluklardan panik bozukluk (PB) (7) ve obsesifkompulsif bozukluk (OKB) (8)'deki TKS verilerine de literatür vasıtasıyla ulaşılmaktadır.…”
Section: Introductionunclassified